THE EFFECT OF USING THE PROBLEM BASED LEARNING MODEL ON STUDENTS’ PROCEDURE TEXT IN WRITING SKILL AT THE EIGHT GRADE OF SMP NEGERI 3 BINJAI - Conny Conny; Muhammad Farhan; Efrini Panjaitan; Ummi Umara (Program Studi Pendidikan Biologi, 2026)
This research aims to determine the effect of the Problem Based Learning (PBL) model on the writing ability of class VIII students of SMP Negeri 3 Binjai. The problem in this study is the low ability of students to write procedural texts. This research uses quantitative methods with quasi-experimental nonequivalent design and pre-test & post-test. The population of this research was 188 students with a sample of 30 student from experimental classes and 30 student from control classes. The sample was taken by purposive sampling. The research instrument was an essay test on writing procedure texts. The result of Independent Samples T Test analysis shown that the significance (sig) 2-tailed value 0.00 was lower than the significance level (0.05) and determined that coefficient of tcounted was -5.390 indicating higher than the ttable coefficient (2.002) with significance level (α) = 0.00 (2-tailed) with degree of freedom (df) = 58, which those results shown that Ha was accepted and H0 was rejected